2017
DOI: 10.1016/j.biopsych.2016.06.025
|View full text |Cite
|
Sign up to set email alerts
|

CRTC1 Function During Memory Encoding Is Disrupted in Neurodegeneration

Abstract: These findings reveal a critical role of CRTC1 in the hippocampus during associative memory, and provide evidence that CRTC1 deregulation underlies memory deficits during neurodegeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 74 publications
2
39
0
Order By: Relevance
“…Recent studies suggest important roles for CRTC1 in synaptic plasticity (Kovacs et al, 2007; Zhou et al, 2006) and memory (Hirano et al, 2013; Nonaka et al, 2014; Parra-Damas et al, 2014; Sekeres et al, 2012). Although CRTC1 has been shown to move from the synapse/dendrite to the nucleus in response to neural activity and learning (Ch'ng et al, 2012; Nonaka et al, 2014; Parra-Damas et al, 2016), it remains unclear how CRTC1 acts during memory formation, what shuttling mechanisms are, and how CRTC1 activates target gene transcription independently of CREB phosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest important roles for CRTC1 in synaptic plasticity (Kovacs et al, 2007; Zhou et al, 2006) and memory (Hirano et al, 2013; Nonaka et al, 2014; Parra-Damas et al, 2014; Sekeres et al, 2012). Although CRTC1 has been shown to move from the synapse/dendrite to the nucleus in response to neural activity and learning (Ch'ng et al, 2012; Nonaka et al, 2014; Parra-Damas et al, 2016), it remains unclear how CRTC1 acts during memory formation, what shuttling mechanisms are, and how CRTC1 activates target gene transcription independently of CREB phosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report has shown that two phosphorylation sites (S151 and S245) contribute to nuclear import of CRTC1 (Nonaka et al, 2014). The nuclear transport of CRTC1 is observed in the CA1 and CA3 pyramidal neurons, but not in the dentate gyrus granule neurons, of the hippocampus following multiple behavioral tasks, including contextual fear conditioning (CFC), novel object location and Morris water maze (Parra-Damas et al, 2017; Uchida and Shumyatsky, 2017; Uchida et al, 2017a). Importantly, strong training of CFC induces much greater CRTC1 nuclear accumulation than weak CFC training (Uchida et al, 2017a), suggesting an association of CRTC1 nuclear translocation with memory strength.…”
Section: Crtc1-creb Signaling In Memory Enhancementmentioning
confidence: 99%
“…In the nucleus, CRTC1 increases the expression of a subset of CREB target genes, including c-fos, Arc, Nr4a1, Bdnf (Ch'ng et al, 2012; Fukuchi et al, 2015; Nonaka et al, 2014; Parra-Damas et al, 2017; Parra-Damas et al, 2014; Zhou et al, 2006a) (Fig. 1).…”
Section: Crtc1-creb Signaling In Memory Enhancementmentioning
confidence: 99%
See 2 more Smart Citations